Systematic review: Clinical outcomes of discontinuation of oral antivirals in hepatitis B-related liver cirrhosis - Yao, Yuhao; Zhang, Jiaxin; Li, Xiaoke; Zao, Xiaobin; Cao, Xu; Chen, Guang; Ye, Yong'an (Frontiers in Public Health, 2022)
Background The feasibility and safety of Nucleos(t)ide analogues (NAs) discontinuation remains one of the most controversial topics in the management of hepatitis B-related liver cirrhosis. Aim The aim of this systematic review is to evaluate the feasibility, safety, and potential benefits of NAs withdrawal in chronic hepatitis B (CHB) patients with cirrhosis. Methods A literature search (until May 2022) was performed in order to identify all published studies including hepatitis B-related cirrhosis patients who discontinued NAs in virological remission with off-therapy follow-up > 12 months. Results 19 studies with 1,287 hepatitis B-related cirrhosis patients were included. The pooled proportions of virological relapse and clinical relapse after NAs discontinuation in cirrhosis patients were 55.23% (95% CI: 40.33 - 69.67) and 43.56% (95% CI: 26.13 - 61.85), respectively. HBsAg loss was observed in 56 of 500 (pooled proportion = 13.68%, 95% CI: 5.82 - 24.18) cirrhotic patients. And the pooled proportions of HCC development, hepatic decompensation and overall mortality were 8.76% (95% CI: 2.25 - 18.95), 3.63% (95% CI: 1.31 - 7.03) and 0.85% (95% CI: 0.35 - 1.57), respectively, after NAs discontinuation in cirrhotic patients. Conclusion In hepatitis B-related cirrhosis, discontinuation of oral antivirals still carries a high relapse rate, but the incidence of adverse events is generally low and controlled, and contributes to the fact that discontinuation NAs achieves a high rate of HBsAg seroclearance. In summary, cessation of NAs in virological remission may be a feasible and worthwhile alternative to indefinite treatment in hepatitis B-related compensated cirrhotic patients.